(untitled) (Scientific journal of the Fergana State University, 2025)
Language is more than words and grammar—it’s how we speak and the context we use. Paralinguistics adds meaning through tone, pitch, and rhythm, like the melody in speech. Sociolinguistics explores how we adapt language based on who we’re speaking to and where. We talk differently with friends than with a boss, reflecting social roles. Together, these fields enhance communication—improving teaching, making media more inclusive, and bridging cultural gaps. They reveal the richness of human interaction, helping us connect more meaningfully.